The Development of Cross-Sector Interorganizational Exchange Relationship Scale - Rembulan, Cicilia Larasati; Helmi, Avin Fadilla; Andayani, Tri Rejeki (Jurnal Psikologi, 2025)
Cross-sector interorganizational exchanges are essential to meeting the needs of all parties involved. However, existing scales to evaluate such exchanges are scarce and are predominantly developed in Western contexts, which differ from Asia’s collectivist nature. This study developed a scale to assess interorganizational exchange relationships. Study 1 employed Straussian grounded theory with participants representing state-owned enterprises and community groups, using interviews and focus group discussions. Data were analysed using the Corbin and Strauss method, and the findings informed the item development for Study 2. Validity evidence based on the test construct was examined using the Content Validity Ratio (CVR) with 20 participants, and item discrimination indices were calculated. Subsequently, data from 178 respondents were analysed through confirmatory factor analysis (CFA). The CFA results indicated that a unidimensional 27-item model provided the best fit, differing from the five dimensions identified in the qualitative study. Nonetheless, no relationship-related items were removed, highlighting the central role of relationships in interorganizational exchange within a collectivist society such as Indonesia.